Clinical and genetic characteristics of rare congenital adrenal hyperplasia: a retrospective analysis in a Chinese population - Chan, Kam; Guo, Ying; Zhang, Shaoling; Yan, Li (Frontiers in Genetics, 2026)
ObjectiveRare subtypes of congenital adrenal hyperplasia (CAH) often present with heterogeneous and overlapping clinical features, leading to substantial diagnostic delays and misclassification. This study aimed to characterize the clinical, biochemical, and genetic profiles of rare CAH types in a Chinese cohort and to identify key diagnostic clues that support early differentiation of these uncommon forms.MethodsWe conducted a single-center retrospective study involving 12 confirmed Chinese cases with rare forms of CAH. Clinical data, including phenotypic features, hormonal profiles, and genetic mutations, were meticulously collected and analyzed.ResultsThe cohort comprised 11β-hydroxylase deficiency (11-OHD, n = 3), 3β-hydroxysteroid dehydrogenase type 2 deficiency (3β-HSD2D, n = 1), lipoid CAH (LCAH, n = 4), aldosterone synthase deficiency (ASD, n = 2), and 17α-hydroxylase deficiency (17-OHD, n = 2). Distinctive clinical constellations that facilitated subtype differentiation included: low-renin hypertension with hyperandrogenism in 11-OHD; isolated hypospadias without salt-wasting in 3β-HSD2D; life-threatening neonatal salt-wasting with global steroid deficiency in LCAH; salt-wasting without virilization in ASD; and late-onset hypertension with sexual infantilism in 17-OHD. Molecular analysis identified six novel pathogenic variants across the CYP11B1, HSD3B2, StAR, CYP11A1, and CYP11B2 genes, expanding the mutational spectrum.ConclusionThese results broaden the existing understanding of the mutational landscape underlying rare CAH and reaffirm that comprehensive clinical and genetic evaluation is essential for differentiating these diagnostically challenging subtypes. By improving early detection and enabling more precise, individualized management, this study provides valuable insights that may substantially advance clinical practice and patient care in rare endocrine disorders.